Benign scalp lump as an unusual presentation of extranodal Rosai-Dorfman disease - Chen, Min Wei (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Rosai–Dorfman disease (RDD) is a rare benign histioproliferative disease. It is typically characterized by benign histiocyte proliferation with lymphadenopathy, fever, and leukocytosis and was first described in 1969 by Rosai and Dorfman. Extranodal involvement has been reported in approximately up to 43% of the cases with isolated central nervous system (CNS) manifestations being even rarer. CASE DESCRIPTION: We report our management of a 41-year-old female with extranodalpurely CNS RDD presenting as a benign scalp lump. Her lump progressed from an asymptomatic benign lesion to one causing localized cerebral edema. Treatment was surgical excision of both the cervical and CNS lesions achieving complete removal of the lesions and resolution of her symptoms. CONCLUSION: RDD is a rare condition and isolated CNS RDD is even less common. Benign scalp lumps have a myriad of differential diagnoses, but RDD should be a consideration in the presence of preexisting RDD lesions at other sites given its potential to progress and result in morbidity. It is imperative to be aware that symptoms may be especially deceiving as the absence of lymphadenopathy may point away from RDD as the diagnosis.